2016
DOI: 10.3171/2016.9.focus16325
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of craniopharyngiomas in the era of genomics and targeted therapy

Abstract: Craniopharyngiomas are rare intracranial neoplasms that pose clinical challenges due to their location adjacent to vital structures. The authors have previously shown high mutation rates of BRAF V600E in papillary craniopharyngioma and of CTNNB1 in adamantinomatous craniopharyngioma. These activating driver mutations are potential therapeutic targets, and the authors have recently reported a significant response to BRAF/MEK inhibition in a patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 42 publications
0
25
0
4
Order By: Relevance
“…In our current era of genomics and molecular targeted therapies, it has been established that the vast majority of adamantinomatous craniopharyngioma and papillary craniopharyngioma present exclusive clonal driver mutations in the CTNNB1 and BRAF genes . The latter is responsible for activation/regulation of mitogen‐activated protein kinase (MAPK) signaling pathways, thus conferring growth advantage through modulation of cell proliferation, differentiation, and cell survival.…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…In our current era of genomics and molecular targeted therapies, it has been established that the vast majority of adamantinomatous craniopharyngioma and papillary craniopharyngioma present exclusive clonal driver mutations in the CTNNB1 and BRAF genes . The latter is responsible for activation/regulation of mitogen‐activated protein kinase (MAPK) signaling pathways, thus conferring growth advantage through modulation of cell proliferation, differentiation, and cell survival.…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…24,25 The most widely observed mutation, CTNNB1, occurs in more than 90% of adamantinomatous craniopharyngiomas, and results in abnormal accumulation of β-catenin, an important player in canonical Wnt signaling pathway and therefore cell differentiation and proliferation. 25,26 This may provide a useful disease marker-inroads are currently being made toward serum-based cell free deoxyribonucleic acid (DNA) assays, which may lead to biopsy-free diagnostic testing-however, β-catenin is a nearly universal player in cellular homeostasis, and the development of specific Wnt pathway inhibitors has been challenging. 24,26 Other studies have demonstrated increased expression of both sonic hedgehog (SHH) and its receptor PTCH1 in adamantinomatous craniopharyngioma, often in patterns correlating with epithelial palisades and co-localizing with β-catenin, indicating a potential autocrine-paracrine mechanism.…”
Section: Transcriptomic Characteristicsmentioning
confidence: 99%
“…25,26 This may provide a useful disease marker-inroads are currently being made toward serum-based cell free deoxyribonucleic acid (DNA) assays, which may lead to biopsy-free diagnostic testing-however, β-catenin is a nearly universal player in cellular homeostasis, and the development of specific Wnt pathway inhibitors has been challenging. 24,26 Other studies have demonstrated increased expression of both sonic hedgehog (SHH) and its receptor PTCH1 in adamantinomatous craniopharyngioma, often in patterns correlating with epithelial palisades and co-localizing with β-catenin, indicating a potential autocrine-paracrine mechanism. 26 Vismodegib is a smoothened inhibitor that acts on the SHH pathway and is FDA approved for the treatment of basalcell carcinoma, as well as undergoing active clinical trials in pediatric medulloblastoma.…”
Section: Transcriptomic Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations